The continuing value of mesalazine as first-line therapy for patients with moderately active ulcerative colitis - Paridaens, Kristine; Freddi, Matthew J.; Travis, Simon P. L. (Frontiers in Gastroenterology, 2024)
Mesalazine is an established and recommended first-line treatment for mild-to-moderate ulcerative colitis (UC). For patients with moderately active UC, the choice to use mesalazine or to initiate treatment with an oral corticosteroid or anti-tumor necrosis factor (TNF) agent is not clearly informed from current guidelines. The use of mesalazine is supported by robust clinical evidence supporting its efficacy at inducing remission in patients with moderately active disease. A key advantage of mesalazine is its tolerability profile being similar to that of placebo, which contrasts with that of the corticosteroids and advanced therapies, where there is the potential for significant toxicities. Mesalazine also has cost advantages over anti-TNFs and other advanced therapies. Evidence supports the consideration of all patients with moderately active UC for first-line mesalazine therapy at an optimized dose of ≥4g/d (± 1g/d rectal). Patients responding to treatment within 2 weeks should continue at ≥4g/d for at least 6 months before a dose reduction is considered, since this then alters the pattern of disease.